Resin-based hard carbon negative electrode material, preparation method thereof and ion battery
Patent Information
- Application Number
- CN202610793569.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-09
AI Technical Summary
但是该方法较为复杂,需要控制的点较多,不适合大规模生产;CN117658106A公开了硬碳材料、硬碳负极材料、电池及硬碳材料的制备方法,通过将硬碳前驱体进行高温碳化,并将碳化阶段的保温时间缩短,导致闭孔数量减少,从而提高容量
[0044]本发明的有益效果是:本发明的树脂基硬碳负极材料具有丰富的闭孔结构,能显著减少与电解液的接触面积,抑制界面副反应,提高首次库仑效率;同时闭孔结构为钠离子提供稳定的低电位储存位点,大幅提升平台区容量和能量密度,且兼具优异的倍率性能和长循环稳定性,具体为:首次充放电比容量为332-370 mAh/g,首次库伦效率为88-95%,低电位平台区容量为260-320 mAh/g。
Smart Images

Figure FT_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conductive materials technology, specifically relating to a resin-based hard carbon anode material, its preparation method, and an ion battery. Background Technology
[0002] In sodium-ion battery anode material systems, although graphite exhibits stable cycle performance, its theoretical specific capacity (372 mAh / g) is insufficient to meet the demands of high-energy-density energy storage. Hard carbon materials, with their unique disordered carbon layer structure (interlayer spacing 0.37-0.42 nm), abundant microstructure, and surface defect sites, demonstrate excellent sodium storage capacity, while also possessing superior rate performance and low-temperature characteristics, making them a research hotspot for next-generation anode materials.
[0003] Among existing hard carbon precursors, biomass materials (coconut shells, bamboo, etc.) are inexpensive, but their complex composition leads to uneven pore distribution in the carbonization products, resulting in first-cycle efficiency generally below 80%. While pitch-based materials offer high carbonization yields, high-temperature treatment easily causes pore closure, leading to significant capacity loss in the plateau region. In contrast, phenolic resins have a simpler and more controllable molecular structure, providing great flexibility for hard carbon preparation. After pyrolysis and carbonization, the unique layered and microporous structure of phenolic resins allows for rapid sodium ion insertion and extraction, exhibiting excellent rate performance. However, hard carbon still suffers from low first-cycle coulombic efficiency and relatively low capacity.
[0004] To improve the sodium storage performance of hard carbon materials, constructing a closed-pore structure through multi-scale structural optimization and functional regulation is an effective approach. The closed-pore structure can reduce the contact area between hard carbon and electrolyte, suppress interfacial side reactions, and provide stable storage sites for sodium ions, thereby improving the battery's initial coulombic efficiency and low-potential plateau capacity.
[0005] In the prior art, CN119092703A discloses a hard carbon anode material, a method for preparing the hard carbon anode material, and a sodium-ion battery. This method controls the proportion of closed-cell structures by adjusting the heating curve of the carbonization temperature, system pressure, and atmosphere, thereby improving the reversible specific capacity and initial coulombic efficiency. However, this method is relatively complex, requiring control of many points, and is not suitable for large-scale production. CN117658106A discloses a hard carbon material, a hard carbon anode material, a battery, and a method for preparing the hard carbon material. This method involves high-temperature carbonization of the hard carbon precursor and shortening the holding time during the carbonization stage, resulting in a reduction in the number of closed cells and thus increasing capacity. However, this leads to the formation of more open pores, resulting in an excessively large specific surface area or the formation of a solid electrolyte interface film, thereby reducing the initial coulombic efficiency and deteriorating cycle stability. Therefore, developing a simple, low-energy-consumption, and scalable method for controlling the closed-cell structure is of great significance for improving the sodium storage performance of resin-based hard carbon anode materials. Summary of the Invention
[0006] In order to overcome at least one of the technical problems existing in the prior art, one of the objectives of the present invention is to provide a resin-based hard carbon anode material.
[0007] The second objective of this invention is to provide a method for preparing a resin-based hard carbon anode material.
[0008] The third objective of this invention is to provide an ion battery.
[0009] The fourth objective of this invention is to provide an electrical device.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a resin-based hard carbon anode material having a true density of 1.50-2.10 g / cm³. 3 Median particle size D 50 It is 6-9 μm; The resin-based hard carbon anode material has a layered structure, and the interlayer spacing d is measured by X-ray diffraction. 002 The wavelength range is 0.371-0.395 nm.
[0011] In some embodiments of the present invention, the true density of the resin-based hard carbon anode material is 1.5 g / cm³. 3 1.6 g / cm 3 1.7 g / cm 3 1.8 g / cm 3 1.9 g / cm 3 2.0 g / cm 3 2.1 g / cm 3 The range of values formed by any one of the values in the range, or any two of them.
[0012] In some embodiments of the present invention, the specific surface area of the resin-based hard carbon anode material is 2-16 m². 2 / g; In some embodiments of the present invention, the specific surface area of the resin-based hard carbon anode material is 2 m². 2 / g、3 m 2 / g、4 m 2 / g、5 m 2 / g、6 m 2 / g、7 m 2 / g、8 m 2 / g、9 m 2 / g、10 m 2 / g、11 m 2 / g、12 m 2 / g、13 m 2 / g、14 m2 / g, 15m 2 / g、16 m 2 Any value in / g or a range of values formed by any two of them.
[0013] In some embodiments of the present invention, the median particle size D of the resin-based hard carbon anode material is... 50 It is a range of values formed by any one of 6μm, 7μm, 8μm, 9μm, or any combination thereof.
[0014] In some embodiments of the present invention, the interlayer spacing d of the resin-based hard carbon anode material 002 It is a range of values formed by any one of 0.371 nm, 0.375 nm, 0.380 nm, 0.385 nm, 0.390 nm, 0.395 nm, or any combination thereof.
[0015] In some embodiments of the present invention, the closed-cell rate of the resin-based hard carbon anode material is ≥6.5%; in some embodiments of the present invention, the closed-cell rate of the resin-based hard carbon anode material is 6.5-12%; in some embodiments of the present invention, the closed-cell rate of the resin-based hard carbon anode material is 6.9-10.4%.
[0016] In some embodiments of the present invention, the porosity of the resin-based hard carbon anode material is ≤12%; in some embodiments of the present invention, the porosity of the resin-based hard carbon anode material is 8-12%; in some embodiments of the present invention, the porosity of the resin-based hard carbon anode material is 8-11.5%.
[0017] The second aspect of the present invention provides a method for preparing the resin-based hard carbon anode material described in the first aspect of the present invention, comprising the following steps: The methyl phenolic resin solution was cured to obtain the cured product; The solidified material is pre-carbonized to obtain a pre-carbonized material; The precarbide is carbonized at a temperature ≥1300℃ to obtain the resin-based hard carbon anode material. The maximum curing temperature shall not be lower than 70°C; The curing time shall not be less than 26 hours.
[0018] The charge-discharge curve of hard carbon anode materials consists of a high-potential ramp region and a low-potential plateau region, with the low-potential plateau region playing a decisive role in the energy density of sodium-ion batteries. In hard carbon, constructing closed pores (hereinafter referred to as closed pores) is an effective method to improve the capacity of its low-potential plateau region. This invention directly regulates the true density of hard carbon anode materials by precisely controlling parameters such as curing temperature, curing time, and carbonization temperature, and indirectly optimizes the proportion of closed-pore structures. This solves the problems of low initial coulombic efficiency, insufficient specific capacity, and complex preparation processes in existing hard carbon anode materials, enabling the prepared hard carbon anode materials to possess high energy density, excellent rate performance, and long-cycle stability. Furthermore, the process is simple, energy-efficient, and cost-controllable, making it suitable for large-scale production.
[0019] In some embodiments of the present invention, the methyl phenolic resin solution is obtained by heating and mixing formaldehyde, phenol, an alkaline catalyst and water; in some embodiments of the present invention, the methyl phenolic resin solution is obtained by heating and mixing formaldehyde, phenol, an alkaline catalyst and water, and then removing the water.
[0020] In some embodiments of the present invention, the step of removing water is achieved by vacuum distillation.
[0021] In some embodiments of the present invention, the alkaline catalyst includes at least one of sodium hydroxide and potassium hydroxide.
[0022] In some embodiments of the present invention, the mass of the alkaline catalyst is 0.5-2% of the mass of phenol; in some embodiments of the present invention, the mass of the alkaline catalyst is 0.8-1.2% of the mass of phenol.
[0023] In some embodiments of the present invention, the solid content of the methyl phenolic resin solution is 40-80%.
[0024] In some embodiments of the present invention, the molar ratio of formaldehyde to phenol is 1:(1-1.5); in some embodiments of the present invention, the molar ratio of formaldehyde to phenol is any value of 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range formed by any two of them.
[0025] In some embodiments of the present invention, the heating and mixing temperature is 65-90°C; in some embodiments of the present invention, the heating and mixing temperature is 70-85°C.
[0026] In some embodiments of the present invention, the heating and mixing time is 1-5 hours; in some embodiments of the present invention, the heating and mixing time is 1-3 hours.
[0027] In some embodiments of the present invention, the curing temperature is 55-200°C; in some embodiments of the present invention, the curing temperature is any value or a range formed by any two of the following: 55°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, and 200°C.
[0028] In some embodiments of the present invention, the curing holding time is 26-60 hours; in some embodiments of the present invention, the curing holding time is any value or a range formed by any two of the following: 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 35 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 45 hours, 46 hours, 48 hours, 50 hours, 52 hours, 54 hours, 55 hours, 56 hours, 58 hours, and 60 hours.
[0029] In some embodiments of the present invention, the curing is performed using one-step curing or gradient curing.
[0030] In some embodiments of the present invention, the gradient curing involves first heating to 55-65°C for 8-15 hours, and then heating to 75-90°C for 30-40 hours.
[0031] In some embodiments of the present invention, the pre-carbonization temperature is 600-1000°C; in some embodiments of the present invention, the pre-carbonization temperature is any value of 600°C, 700°C, 800°C, 900°C, 1000°C, or a range formed by any two of them.
[0032] In some embodiments of the present invention, the heating rate of the pre-carbonization is 2-10℃ / min; in some embodiments of the present invention, the heating rate of the pre-carbonization is any value of 2℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 8℃ / min, 10℃ / min or a range formed by any two of them.
[0033] In some embodiments of the present invention, the pre-carbonization holding time is 3-6 hours; in some embodiments of the present invention, the pre-carbonization holding time is any value of 3 hours, 4 hours, 5 hours, 6 hours or a range formed by any two of them.
[0034] In some embodiments of the present invention, the carbonization temperature is 1300-1600°C; in some embodiments of the present invention, the carbonization temperature is any value of 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, or a range formed by any two of them.
[0035] In some embodiments of the present invention, the carbonization holding time is 2-6 hours; in some embodiments of the present invention, the carbonization holding time is any value of 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or a range formed by any two of them.
[0036] In some embodiments of the present invention, the heating rate of carbonization is 1-8°C / min; in some embodiments of the present invention, the heating rate of carbonization is any value of 1°C / min, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, or a range formed by any two of these values.
[0037] In some embodiments of the present invention, both the carbonization and the pre-carbonization are carried out under a protective atmosphere.
[0038] In some embodiments of the present invention, the protective atmosphere includes at least one selected from nitrogen, argon, helium, xenon, and neon; in some embodiments of the present invention, the protective atmosphere is nitrogen. Nitrogen is inexpensive, readily available, and effectively isolates the material from air, preventing oxidation.
[0039] In some embodiments of the present invention, the preparation method further includes a pulverizing step; the pulverizing step is performed after the carbonization.
[0040] In some embodiments of the present invention, the pulverization step involves pulverizing the resin-based hard carbon anode material to a median particle size D50 of 6-9 μm.
[0041] A third aspect of the present invention provides an ion battery including a negative electrode; the negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector; the negative electrode active layer contains the resin-based hard carbon negative electrode material described in the first aspect of the present invention.
[0042] In some embodiments of the present invention, the ion battery includes a sodium-ion battery, a lithium-ion battery, or a potassium-ion battery.
[0043] A fourth aspect of the present invention provides an electrical device comprising the ion battery described in the third aspect of the present invention.
[0044] The beneficial effects of this invention are as follows: The resin-based hard carbon anode material of this invention has abundant closed-pore structure, which can significantly reduce the contact area with the electrolyte, suppress interfacial side reactions, and improve the initial coulombic efficiency; at the same time, the closed-pore structure provides stable low-potential storage sites for sodium ions, greatly improving the plateau capacity and energy density, and also has excellent rate performance and long-term cycle stability, specifically: the initial charge-discharge specific capacity is 332-370 mAh / g, the initial coulombic efficiency is 88-95%, and the low-potential plateau capacity is 260-320 mAh / g.
[0045] The preparation method of this invention uses methyl phenolic resin as a precursor. The molecular structure of methyl phenolic resin is controllable and has good stability, making it easy to store and subsequently cure. Compared with biomass and pitch-based precursors, it can more precisely control the microstructure of hard carbon anode materials. In addition, the preparation method of this invention is simple, has low energy consumption, controllable cost, and can be mass-produced, which is of great significance for improving the sodium storage performance of resin-based hard carbon anode materials.
[0046] This invention regulates the true density of hard carbon anode materials by precisely controlling parameters such as curing temperature and carbonization temperature, thereby optimizing the proportion of closed-cell structures. It eliminates the need for complex pressure control or multi-stage heating curve design, making the process simple, easy to operate, and reducing equipment energy consumption and production difficulty. Attached Figure Description
[0047] Figure 1 The image shows the X-ray diffraction pattern of the hard carbon anode material in Example 1. Detailed Implementation
[0048] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described in detail below are those that can be implemented or understood by those skilled in the art by referring to the prior art. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0049] Example 1 This example demonstrates the preparation of a resin-based hard carbon anode material. The specific preparation process is as follows: (1) Synthesis of methyl phenolic resin: Phenol, formaldehyde and deionized water were mixed in a molar ratio of 1:1.2:2, and NaOH (1.0% of the mass of phenol) was added. The mixture was stirred at 70°C for 2 h. After the reaction was completed, the solution was dehydrated under reduced pressure (vacuum degree 0.09 MPa (gauge pressure), temperature ≤105°C) to obtain methyl phenolic resin solution.
[0050] (2) Curing treatment: The phenolic resin was placed in a forced-air oven and cured by gradient temperature increase: first, it was pre-cured at 60℃ for 12 h, and then the temperature was increased to 85℃ and kept constant for 36 h to obtain a fully cross-linked cured resin block.
[0051] (3) Pre-carbonization treatment: The solidified material is placed in a nitrogen atmosphere tube furnace and heated to 900℃ at a heating rate of 5℃ / min. The temperature is held for 5 h to complete the pre-carbonization and obtain the pre-carbonized material.
[0052] (4) High-temperature carbonization: The pre-carbonized material is heated to 1450℃ in a nitrogen atmosphere at a heating rate of 5℃ / min and held for 3 hours to complete the carbonization and obtain resin-based hard carbon.
[0053] (5) Grinding and classifying: Grind the resin-based hard carbon to the median particle size D. 50 =7μm, thus obtaining the resin-based hard carbon anode material in this example.
[0054] Example 2 This example demonstrates the preparation of a resin-based hard carbon anode material. The specific preparation process is as follows: (1) Synthesis of methyl phenolic resin: Phenol, formaldehyde and deionized water were mixed in a molar ratio of 1:1.5:2, and ammonia water (1.5% of the mass of phenol) was added as an alkaline catalyst. The mixture was stirred at 80°C for 2.5 h. After the reaction was completed, the solution was dehydrated under reduced pressure (vacuum degree 0.09 MPa (gauge pressure), temperature ≤105°C) to obtain methyl phenolic resin solution.
[0055] (2) Curing treatment: The phenolic resin was placed in a forced-air oven and cured at 130°C for 48 h to obtain a fully cross-linked cured resin block.
[0056] (3) Pre-carbonization treatment: The solidified material is placed in a nitrogen atmosphere tube furnace and heated to 950°C at a heating rate of 5°C / min. The temperature is held for 5 hours to complete the pre-carbonization and obtain the pre-carbonized material.
[0057] (4) High-temperature carbonization: The pre-carbonized material is heated to 1500℃ in a nitrogen atmosphere at a heating rate of 5℃ / min and held for 3 h to complete the carbonization and obtain resin-based hard carbon.
[0058] (5) Grinding and classifying: Grind the resin-based hard carbon to the median particle size D. 50 =7μm, thus obtaining the resin-based hard carbon anode material in this example.
[0059] Example 3 This example demonstrates the preparation of a resin-based hard carbon anode material. The specific preparation process is as follows: (1) Synthesis of methyl phenolic resin: Phenol and formaldehyde were mixed with deionized water in a molar ratio of 1:1.8 and 1:1.8:2. KOH (0.8% of the mass of phenol) was added as an alkaline catalyst and stirred at 75°C for 3 h. After the reaction was completed, the solution was dehydrated under reduced pressure (vacuum degree 0.09 MPa (gauge pressure), temperature ≤105°C) to obtain methyl phenolic resin solution.
[0060] (2) Curing treatment: The methyl phenolic resin was placed in a forced-air oven and cured at 150℃ for 48 h to obtain a fully cross-linked cured resin block.
[0061] (3) Pre-carbonization treatment: The solidified material is placed in a nitrogen atmosphere tube furnace and heated to 1000℃ at a heating rate of 5℃ / min. The temperature is held for 5 h to complete the pre-carbonization and obtain the pre-carbonized material.
[0062] (4) High-temperature carbonization: The pre-carbonized material is heated to 1550℃ in a nitrogen atmosphere at a heating rate of 5℃ / min and held for 3 hours to complete the carbonization and obtain resin-based hard carbon.
[0063] (5) Grinding and classifying: Grind the resin-based hard carbon to the median particle size D. 50 =7μm, thus obtaining the resin-based hard carbon anode material in this example.
[0064] Example 4 This example demonstrates the preparation of a resin-based hard carbon anode material. The specific preparation process is as follows: (1) Synthesis of methyl phenolic resin: Phenol, formaldehyde and deionized water were mixed in a molar ratio of 1:1.2:2, and NaOH (1.2% of the mass of phenol) was added as an alkaline catalyst. After the reaction was stirred at 85°C for 2 h, the solution was dehydrated under reduced pressure (vacuum degree 0.09 MPa (gauge pressure), temperature ≤105°C) to obtain methyl phenolic resin solution.
[0065] (2) Curing treatment: The phenolic resin was placed in a forced-air oven and cured at 130°C for 48 h to obtain a fully cross-linked cured resin block.
[0066] (3) Pre-carbonization treatment: The solidified material is placed in a nitrogen atmosphere tube furnace and heated to 950°C at a heating rate of 5°C / min. The temperature is held for 5 hours to complete the pre-carbonization and obtain the pre-carbonized material.
[0067] (4) High-temperature carbonization: The pre-carbonized material is heated to 1500℃ in a nitrogen atmosphere at a heating rate of 2℃ / min and held for 3 h to complete the carbonization and obtain resin-based hard carbon.
[0068] (5) Grinding and classifying: Grind the resin-based hard carbon to the median particle size D. 50 =7μm, thus obtaining the resin-based hard carbon anode material in this example.
[0069] Comparative Example 1 The only difference between this example and the preparation method in Example 1 is that the carbonization temperature in step (4) of this example is 1250℃, while the other steps are the same.
[0070] Comparative Example 2 (Insufficient curing time, impact of crosslinking degree of the comparative resin) The only difference between this example and the preparation method in Example 2 is that the curing time in step (2) of this example is 24 hours, while the other steps are the same. Due to insufficient curing time, the resin crosslinking degree is low, resulting in a loose structure after carbonization, a significant decrease in true density, and an increase in open porosity.
[0071] Comparative Example 3 (lower curing temperature, affecting the degree of crosslinking of the comparison resin) The difference between this example and the preparation method in Example 2 is that the curing temperature in step (2) of this example is 85°C, while the other steps are the same. At this temperature, the crosslinking reaction rate of the resin is relatively slow, resulting in an incomplete crosslinking network, which affects the pore closure in the subsequent carbonization process.
[0072] Comparative Example 4 (pre-carbonization step omitted, comparing the effects of the two-step carbonization process) The only difference between this example and the preparation method in Example 2 is that in this example, pre-carbonization is not performed in step (3), and high-temperature carbonization is performed directly. This leads to excessively rapid pyrolysis of the resin, resulting in severe volume shrinkage and cracking, making it difficult to form a stable closed-cell structure.
[0073] Performance testing: The true density, specific surface area, porosity, closed-cell structure, and battery performance of the resin-based hard carbon anode materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested respectively. The specific test methods are as follows: (1) The true density test method is as follows: The true density was tested using the helium displacement method (helium specific gravity bottle method). The test steps were as follows: (a) Sample pretreatment conditions: The resin-based hard carbon anode material was vacuum dried at 105℃ for 3h to completely remove moisture and adsorbed gases; after drying, it was placed in a desiccator to cool to room temperature and sampled quickly (to prevent secondary water absorption); (b) Test environment conditions: room temperature 25±2℃, humidity ≤60%RH, to avoid water vapor affecting the pore gas discharge; (c) Instruments and media: a helium true density meter was used for testing, and high-purity helium (purity ≥99.999%) was used as the carrier gas to reduce interference from impurity gases; (2) Test methods for specific surface area and open porosity The open pore volume of the material was tested using the nitrogen adsorption-desorption method (BET method) for subsequent calculation of the closed pore rate. The specific steps were as follows: ① Sample pretreatment: The resin-based hard carbon anode material was degassed under vacuum at 200℃ for 6 h to remove the moisture and gas adsorbed on the sample surface; ② Test conditions: Nitrogen adsorption-desorption test was performed in a liquid nitrogen environment at 77 K. The specific surface area of the material was calculated using the BET model, and the open porosity of the material was calculated using the BJH model.
[0074] (3) Small-angle X-ray scattering (SAXS) test method Small-angle X-ray scattering was used to test resin-based hard carbon anode materials to characterize the overall total pore structure of the material, including open and closed pores.
[0075] In this invention, open pores refer to pores that are interconnected inside the porous material and penetrate the outer surface of the material; closed pores refer to closed cavities that are completely enclosed by the matrix and are not connected to the external surface or other pores.
[0076] Test conditions: Cu Kα rays, wavelength λ = 0.154 nm, test range 0.1°~5° (2θ). The total porosity of the material was obtained by fitting and analyzing the scattering curves.
[0077] Formula for calculating closed-pore ratio: Closed porosity (%) = Total porosity measured by SAXS BET measured the open porosity (4) The battery performance test method is as follows: the coin cell half-cell constant current charging method is used for testing. The test conditions are as follows: the resin-based hard carbon negative electrode material, conductive agent Super P, and binder CMC are mixed evenly at a mass ratio of 90:5:5 and slurry is prepared. The slurry is then coated on the copper foil current collector and vacuum dried to form the negative electrode sheet. The sodium metal sheet is used as the counter electrode, the glass fiber porous membrane is used as the separator, and the electrolyte is 1 mol / L NaClO4 solution (solvent is EC:DMC=1:1, volume ratio; 5% FEC is added). The coin cell is assembled in an argon glove box with water and oxygen content of less than 1 ppm and tested after standing for 8 h. The test temperature is 25±2℃ and the voltage window is 0.01~2.5 V (vs Na / Na + ), 0.1C constant current charge and discharge test.
[0078] The low-potential plateau region capacity is defined as the sodium intercalation capacity within the voltage range of 0.01 to 0.1 V, and the capacity contribution of each voltage range is calculated.
[0079] The performance data of the resin-based hard carbon anode materials prepared in Examples 1-4 and Comparative Examples 1-4, obtained according to the above test methods, are shown in Table 1 below.
[0080] Table 1. True density and battery performance test results
[0081] As shown in Table 1, in Examples 1-4, the curing temperature, curing time, carbonization temperature, and heating rate significantly affect the closed-cell structure and physicochemical properties of the negative electrode material, specifically: (1) Influence of curing process: Comparing Examples 1-3, it can be seen that as the curing temperature and time increase (or the degree of crosslinking increases), the resin crosslinks more fully, the gas escape channels are easier to close during carbonization, and the closed-cell rate of the material is significantly improved; at the same time, the gas is more likely to form a stable closed-cell structure inside during carbonization, reducing the collapse of open-cell channels, the open-cell rate and BET specific surface area increase synchronously, and the measured true density shows a downward trend, which confirms each other.
[0082] Comparing Example 3 with Comparative Example 1, the main difference lies in the type of pore structure: Comparative Example 1 has predominantly open pores, resulting in a high BET surface area and open pore porosity, which makes it prone to interfacial side reactions with the electrolyte, leading to a lower initial coulombic efficiency. In contrast, Example 3, through controlling the curing process, significantly improved the closed pore ratio, with both the open pore ratio and BET surface area decreasing simultaneously. Therefore, the initial coulombic efficiency, initial charge specific capacity, and low-potential plateau capacity of the material are significantly better than those of Comparative Example 1. This indicates that the closed-pore structure, rather than the total porosity, is the key factor determining the sodium storage performance of the hard carbon anode, and also confirms the effectiveness of the technical route of improving the performance of the hard carbon anode by controlling the closed-pore structure. The closed-pore structure reduces the direct contact between the carbon material and the electrolyte, suppresses interfacial side reactions, improves the initial coulombic efficiency, and provides stable low-potential storage sites for sodium ions, significantly improving the low-potential plateau capacity.
[0083] (2) Effect of carbonization heating rate: Reducing the heating rate during the carbonization stage is beneficial for controlling the pyrolysis gas release rate and micropore evolution, further promoting the formation of closed-pore structures, and further improving the capacity of the low-potential plateau region. For example, compared with Example 2, by reducing the heating rate during the carbonization stage, the closed-pore ratio of Example 4 is further improved, and the corresponding first coulombic efficiency and low-potential plateau region capacity are significantly improved.
[0084] (3) Comparative Example Analysis: Comparative Example 1 (low-temperature carbonization), Comparative Example 2 (short-time curing), Comparative Example 3 (low-temperature curing), and Comparative Example 4 (no pre-carbonization) all failed to construct a sufficiently effective closed-cell structure. Among them, Comparative Examples 1 and 3 suffered from insufficient carbonization or curing, resulting in insufficient carbon layer order or low resin crosslinking degree, leading to a significant decrease in closed-cell rate (5.5% and 3.0%, respectively, both lower than the highest level in the examples). Comparative Example 2 suffered from insufficient crosslinking, resulting in an excessively loose structure. Although the resin skeleton density remained at a reasonable level, the specific surface area was too large (24.5 m²). 2 The material has a porosity of up to 29% and a closed-cell rate of only 1.0%, with large-sized open pores dominating, resulting in a significant decrease in the overall true density (1.541 g / cm³). 3The inability to form sufficient low-potential sodium storage sites demonstrates that moderate crosslinking and carbonization densification are crucial for closed-cell formation. Comparative Example 4, lacking pre-carbonization treatment, exhibited an unstable resin crosslinking structure, a closed-cell rate of only 4.5%, poor interfacial stability, and an initial coulombic efficiency of only 79.2%, far lower than the examples. This further demonstrates that moderate crosslinking and carbonization densification are essential for closed-cell formation.
[0085] (4) Correlation of electrochemical performance: The closed-pore ratio is highly correlated with the initial coulombic efficiency and the plateau capacity. The closed-pore ratios of Examples 1-4 are all ≥6.9%, and their initial coulombic efficiencies are all above 88%, with low-potential plateau capacities exceeding 260 mAh / g; while in the comparative examples, the closed-pore ratios are generally low (especially Comparative Example 2, which is only 1.0%), and the open-pore ratios and specific surface areas are significantly higher, exacerbating interfacial side reactions and leading to a significant decrease in performance indicators.
[0086] The X-ray diffraction pattern of the resin-based hard carbon anode material prepared in Example 1 was measured using an X-ray diffractometer, as shown in the figure below. Figure 1 As shown. By Figure 1 It can be seen that the (002) characteristic peak appears in the range of 20°-30°, reflecting the carbon interlayer spacing and degree of order, and its d 002 The value is 0.375 nm; a (100) characteristic peak appears in the range of 35°-50°.
[0087] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A resin-based hard carbon anode material, characterized in that: The true density of the resin-based hard carbon anode material is 1.50-2.10 g / cm³. 3 Median particle size D 50 It is 6-9 μm; The resin-based hard carbon anode material has a layered structure, and the interlayer spacing d is measured by X-ray diffraction. 002 The wavelength range is 0.371-0.395 nm.
2. The resin-based hard carbon anode material according to claim 1, characterized in that: The specific surface area of the resin-based hard carbon anode material is 2-16 m². 2 / g; And / or, the closed-cell rate of the resin-based hard carbon anode material is ≥6.5%; And / or, the porosity of the resin-based hard carbon anode material is ≤12%.
3. The method for preparing the resin-based hard carbon anode material according to any one of claims 1-2, characterized in that: Includes the following steps: The methyl phenolic resin solution was cured to obtain the cured product; The solidified material is pre-carbonized to obtain a pre-carbonized material; The precarbide is carbonized at a temperature ≥1300℃ to obtain the resin-based hard carbon anode material. The maximum curing temperature shall not be lower than 70°C; The curing time shall not be less than 26 hours.
4. The method for preparing the resin-based hard carbon anode material according to claim 3, characterized in that: The methyl phenolic resin solution is obtained by heating and mixing formaldehyde, phenol, an alkaline catalyst, and water.
5. The method for preparing the resin-based hard carbon anode material according to claim 4, characterized in that: The solid content of the methyl phenolic resin solution is 40-80%; And / or, the molar ratio of formaldehyde to phenol is 1:(1-1.5).
6. The method for preparing the resin-based hard carbon anode material according to claim 3, characterized in that: The curing temperature is 55-200℃; And / or, the curing time is 26-60 hours; And / or, the pre-carbonization temperature is 600-1000°C; And / or, the heating rate of the pre-carbonization is 2-10 °C / min; And / or, the heat preservation time for pre-carbonization is 3-6 hours; And / or, the carbonization temperature is 1300-1600℃; And / or, the carbonization holding time is 2-6 hours; And / or, the heating rate of the carbonization is 1-8 °C / min.
7. The method for preparing the resin-based hard carbon anode material according to claim 3, characterized in that: Both the carbonization and the pre-carbonization are carried out under a protective atmosphere.
8. The method for preparing the resin-based hard carbon anode material according to claim 3, characterized in that: The preparation method further includes a pulverizing step; the pulverizing step is performed after the carbonization.
9. An ion battery, comprising a negative electrode; characterized in that: The negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector; the negative electrode active layer contains the resin-based hard carbon negative electrode material according to any one of claims 1-2.
10. An electrical appliance, characterized in that: Including the ion battery as described in claim 9.
Citation Information
Patent Citations
Hard carbon material, hard carbon negative electrode material, battery and preparation method of hard carbon material
CN117658106A